Анализ и выявление основных рисков при создании консодированой группы налогоплательщиков в РФ; Менеджмент XXI века: антикризисные стратегии иуправление рисками - Мусина С. З. София Замировна (2015, 2015)
Consolidation gives rise to tax liability risks both for the state and for the member organizations of Consolidated Group of Taxpayers (CGT). Tax risks are paid by Russian companies on their own as well as by the members of CGT, however for them tax risks may vary. There are specific types of risks when creating a CGT or an income tax group of companies. These risks are connected with the terms of entry into CGT; requirements for their members; possible failures to conclude the agreement on CTG establishment; or exit from CTG.